Natural Science Thematic E-Learning Content Development at TK Santo Yoseph Medan - Chatrine Sylvia; Angela Angela; Fandi Halim (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
This community service activity aims to produce learning content which is adapted to the thematic learning concepts applied in TK Santo Yoseph Medan. The learning content for TK Santo Yoseph Medan will be provided in several short videos to elaborate the learning materials according to Natural Science theme. Video is divided into several short videos that are customed to fit the children's interest where each content contains colour images, animations, and brief information according to school material. These videos as the results of this community service activity helps TK Santo Yoseph Medan on improving the learning services by providing quality content for kindergarten students.